THE RELATIONSHIP BETWEEN KNOWLEDGE, TRAINING, AND INFRASTRUCTURE ON THE COMPLIANCE OF HEALTH WORKERS IN APPLYING STANDARD PRECAUTIONS IN HOSPITALS - Fanny, Nabilatul; Sari, Devi Pramita; Nugraini, Alifah Sari (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Compliance with standard precautions among health workers in hospitals is currently still low. Based on the preliminary survey, it is known that the IPCLN has been formed and the PPI program has been created. The infection data found that there was one nurse who was positive for HBsAg, supervision was limited to service matters. The research objective was to determine the relationship between knowledge, training, and infrastructure on the compliance of health workers in applying standard precautions in hospitals. This type of research is a quantitative research that is correlational, with a cross-sectional research design. The population is all nurses in the emergency room, inpatient and outpatient settings. Sampling was taken using Purposive Sampling technique, the sample size was 163 respondents. Univariate and bivariate data analysis. The results showed that 66.2% of respondents had good knowledge, 70.6% had attended training, and 77.3% of respondents answered that the infrastructure was good. Bivariate analysis showed that the knowledge variable had a P value = 0.001 (<0.05), the training variable had a P value = 0.000 (<0.05), and the infrastructure variable had a P value = 0.000 (<0.05). The conclusion is that there is a relationship between knowledge, training, and infrastructure on the compliance of health workers in applying standard precautions. Suggestions that health workers should always apply standard precautions, hospitals can provide ongoing training and education to improve care adherence to standard precautions.